A broad analysis in clinical and in vitro models on regulator of G‐protein signalling 10 regulation that is associated with ovarian cancer progression and chemoresistance. (22nd December 2020) - Kucuk, Burak; Kibar, Beyza; Cacan, Ercan
Abstract : Ovarian cancer is one of the deadliest types of gynaecological cancers and more than half of the patients die within 5 years after diagnosis. Recurrence in advanced staged patients after chemotherapy is associated with increased chemoresistance, which results in poor prognosis. Regulator of G‐protein signalling 10 (RGS10) negatively regulates cell proliferation, migration and survival by attenuating G‐protein coupled‐receptors mediated signalling pathways. Recent studies have shown that loss of RGS10 expression is significantly associated with proliferation and cisplatin resistance in ovarian cancer cells. Significance of the study: In this study, we analysed differential RGS10 expression levels using public microarray datasets from clinical and in vitro ovarian cancer samples. We validated that cancer progression and chemotherapy exposure change RGS10 expression. We enriched our study to evaluate the relationship between chemoresistance and differential RGS10 expression against ovarian cancer potential chemotherapeutic agent, palbociclib. Results showed that palbociclib treatment reduced cell viability, despite significantly decreased RGS10 expression in chemoresistant cells. Overall, the results confirmed that cancer progression and chemoresistance are significantly associated with the down‐regulation of RGS10 while some chemotherapeutics seem to be beneficial in decreasing chemoresistance in ovarian cancer.